PP2A: A Promising Biomarker and Therapeutic Target in Endometrial Cancer - Remmerie, Michiel; Janssens, Veerle (Frontiers in Oncology, 2019)
Over the last decade, the use of targeted therapies has immensely increased in the treatment of cancer. However, treatment for endometrial carcinomas (ECs) has lagged behind, although potential molecular markers have been identified. This is particularly problematic for the type II ECs, since these aggressive tumors are usually not responsive towards the current standard therapies. Therefore, type II ECs are responsible for most EC-related deaths, indicating the need for new treatment options. Interestingly, molecular analyses of type II ECs have uncovered frequent genetic alterations (up to 40%) in PPP2R1A, encoding the Aα subunit of the tumor suppressive heterotrimeric protein phosphatase type 2A (PP2A). PPP2R1A mutations were also reported in type I ECs and other common gynecologic cancers, albeit at much lower frequencies (0-7%). Nevertheless, PP2A inactivation in the latter cancer types is common via other mechanisms, in particular by increased expression of Cancerous Inhibitor of PP2A (CIP2A) and PP2A Methyl Esterase-1 (PME-1) proteins. In this review, we discuss the therapeutic potential of direct and indirect PP2A targeting compounds, possibly in combination with other anti-cancer drugs, in EC. Furthermore, we investigate the potential of the PP2A status PPP2R1A as a predictive and/or prognostic marker for type I and II ECs.